An overview of electronic medical record implementation in healthcare system: Lesson to learn - Khamis, Noraziani; Ahayalimudin, Nurul'Ain (IDOSI Publication, 2013)
Abstract: Introduction: In many countries, healthcare system has been changed by the usage of some form of information technology, predominantly in terms of electronic medical record. Information technology which is deployed effectively, can replace old challenges in providing healthcare services. Objective: The purpose of this article is to discuss on implementation of electronic medical record in healthcare systems globally through SWOT analysis and gather a lesson that can be learn from the progression of the systems. Methodology: A review on the literature through open access journal, PPUKM library portal using key words. Result: Lessons can be learned from existing local and global EMR implementation. EMR implementation provides opportunities to improve health service deliveries in Malaysia. Key words:Electronic medical record Electronic health record Hospital information systems Information technology